Remarkably stable chelating bis-N-heterocyclic carbene adducts of phosphorus(i) cations1. Issue 36 (4th May 2015) - Binder, Justin F.; Swidan, Ala'aeddeen; Tang, Martin; Nguyen, Jennifer H.; Macdonald, Charles L. B.
<x xml:space="preserve">Abstract</x> Treatment of triphosphenium precursors with bidentate bis-N-heterocyclic carbenes generates remarkably stable phosphamethine cyanine dyes with useful chemical and physical properties.